Implementations of Blended Learning from the Al-Qur’an Perspective - Suhada, Suhada; Arief, Armai; Sarnoto, Ahmad Zain (ADI Publisher, 2025)
Blended learning is a relevant learning model to answer the challenges of the 21st century, where technology and the internet play an important role. However, the implementation of blended learning in higher education still faces obstacles in adjusting modern educational values with spiritual values. This study aims to analyze blended learning from the perspective of the Qur'an, with a case study at University of Raharja, Tangerang City. The main challenges raised is how blended learning can be integrated with the values of the Qur'an to create holistic learning. The research method uses a descriptive qualitative approach of the Miles and Huberman model to systematically describe data from various references. In addition, the thematic interpretation method (tafsîr maudhû’î) is used to analyze relevant verses of the Qur'an. The results of the study indicate that blended learning is in accordance with the learning values in the Qur'an, as reflected in the stories of the prophets and verses about learning from the universe. This model has proven to be flexible, efficient, and effective, as supported by Curtis J. Bonk, Simon Krisztián, and Erica Lynn Kolat. This study also found that blended learning can be a relevant learning solution in the digital era if implemented by considering spiritual aspects. The conclusion of the study is that blended learning not only supports modern learning, but also has a strong foundation in the values of the Qur'an. This makes an important contribution to the development of higher education in Indonesia.